P066 Validation of assay for detection of free soluble mucosal addressin cell adhesion molecule-1 (MAdCAM-1) in human serum and cerebrospinal fluid. (25th January 2019) - Fernandez Ocana, M; Zhang, J Y; Jones, B R; Martin, S W; Goetsch, M; Neubert, H
Abstract: Background: Mucosal addressin cell adhesion molecule-1 (MAdCAM-1) plays a key role in gut immune surveillance and homing of α4β7 integrin-expressing lymphocytes to the gut mucosa during inflammation. MAdCAM-1 is predominantly expressed on the endothelium of high endothelial venules in the gut and gut-associated lymphoid tissue, and is not constitutively expressed in the CNS. SHP647 is a fully human monoclonal anti-MAdCAM-1 antibody in development for the treatment of ulcerative colitis and Crohn's disease. To better understand the relationship between SHP647 target engagement (binding to MAdCAM-1) and downstream clinical effects, we developed an assay to measure free concentrations of MAdCAM-1 in both serum and cerebrospinal fluid (CSF). Methods: The assay was a hybrid of immunocapture and nano liquid chromatography–tandem mass spectrometry (LC–MS/MS). Biotinylated SHP647 was used as a capture agent, followed by trypsin digestion and LC–MS/MS for separation and detection, respectively. The immunocapture conditions of the assay were optimised to provide good recovery of endogenous MAdCAM-1 levels using low concentrations of biotinylated SHP647 under a short incubation time. Assay performance was assessed in human serum and CSF from healthy donors and donors with inflammatory bowel disease. Results: Inter-assay and intra-assay precision and relative accuracy were acceptable (relative standard deviation ≤25% and ±25%, , respectively) in human serum and CSF. Calibration standard responses for free soluble MAdCAM-1 were linear over the range of 0.5–512 pM in serum and 0.5–30 pM in CSF; using a weighted (1/concentration 2 ) linear least squares regression. To test whether the assay was selective to measure free soluble MAdCAM-1 in serum, an excess of SHP647 (500 times the endogenous concentration of MAdCAM-1) was added to blank serum samples allowing existing endogenous MAdCAM-1 to bind to the drug. Mean MAdCAM-1 detected fell from 325 pM to 1.95 pM, demonstrating that the assay is selective for free soluble MAdCAM-1 in serum without measuring soluble MAdCAM-1 bound to SHP647. Soluble MAdCAM-1 in serum and CSF samples was stable at 4°C up to 24 h and over 5 freeze/thaw cycles at –20°C and –70°C; CSF samples were stable up to 182 days at –20°C and –70°C, and serum samples were stable for 577 days at –70°C and 381 days at –20°C. Conclusions: The immunocapture LC–MS/MS assays described are valid for the detection of free soluble MAdCAM-1 in human serum and CSF samples within the investigated concentration ranges. In serum, the assay was shown to be selective and sensitive for free soluble MAdCAM-1 not bound to SHP647. These data support the use of these immunocapture LC–MS/MS assays for the detection of free MAdCAM-1 in serum and CSF in clinical trials.